Pemimpin Indonesia Masa Depan - T. Jacob (Universitas Islam Indonesia, 2004)
Leader means the head of government, the members of cabinet, those of executive, judicative. legislative and the leaders of political parties. Departing from afore explana tion, it is clear that the leader that Indonesian people need is the leader who can solve the problems of this nation. As leader, he or she should have collective and future oriented. The leader must have decisional competence, tolerant and morality attitude. Besides, acceptability of the leader denotes political basic and the cultural foundation.